Оцінювання ефективності диверсифікування географічної структури зовнішньоекономічної діяльності в умовах євроінтеграції - Руда, М. В.; Пилипенко, А. О.; Ruda, M. V.; Pylypenko, A. O. (Видавництво Львівської політехніки, 2023)
Визначено сутність поняття диверсифікації, наведено її види та особливості цієї стратегії освоєння нових ринків. Проаналізовано фактори, що впливають на ефективність диверсифікування географічної структури зовнішньоекономічної діяльності ТОВ “НОВА ПОШТА”. Окреслено передумови необхідності імплементації стратегії географічної диверсифікації зовнішньоекономічної діяльності, описано можливості та загрози, які можуть виникнути під час розширення діяльності на ринках ЄС. Визначено особливості GoToMarket-стратегії, розроблено етапи реалізації маркетингової стратегії з урахуванням національних і міжнародних особливостей ринку та моделей споживання послуг в умовах диверсифікування географічної структури зовнішньоекономічної діяльності. Сформовано бізнес-індикатори для оцінювання ефективності диверсифікування географічної структури зовнішньоекономічної діяльності ТОВ “НОВА ПОШТА”.

An analysis and assessment of factors influencing the effectiveness of diversification of the geographical structure of foreign economic activity of "NOVA POSHTA" LLC was carried out. The essence of the concept of diversification is determined, its types and features of this strategy of developing new markets are given. The prerequisites for the implementation of the strategy of geographical diversification of foreign economic activity, the opportunities and threats that may arise during the expansion of activities in the EU markets are outlined. Diversification of foreign economic activity is caused by increasing the dynamism of enterprise development, changes in demand and the emergence of new industries on the market. In such cases, the diversification makes it possible to compensate for the drop in sales in one market by increasing it in other markets. It also contributes to attracting foreign investments and increasing the competitiveness of the enterprise. All types of geographic diversification open up new business opportunities for enterprises – business entities can make maximum use of resource potential and production capacity, distribute commercial risks of dependence on one market and minimize them. Nowadays, logistics as an industry has great potential and prospects. According to the forecast, until 2024, the world market of logistics services will grow annually by 7.5 % in monetary terms. The main players on the market in Ukraine are "NOVA POSHTA" and "Ukrposhta". This is due to the fact that more and more people are switching to online shopping. As a result of the conducted research, it was determined that in modern business conditions, the strategy of diversifying the geographical structure of foreign economic activity is becoming more and more relevant, but it must be supported by empirical data coming from the marketing monitoring system. Assessing the necessity of diversifying the geographical structure of foreign economic activity in case of "NOVA POSHTA" LLC requires consideration of many factors, especially resources, financial capacity and taxation. Taking them into account the recommended directions for the implementation of the GoToMarket-strategy for "NOVA POSHTA" LLC are given in the article. The stages of marketing strategy implementation considering national and international market features and service consumption models of "NOVA POSHTA" LLC in conditions of diversification of the geographical structure of foreign economic activity are outlined. Recommended business indicators for evaluating the effectiveness of diversifying the geographical structure of foreign economic activity of "NOVA POSHTA" LLC are identified.
Assessment of efficiency of diversifying the geographical structure of foreign economic activities in the conditions of European integration
Keywords: диверсифікація; стратегія диверсифікування; географічна структура ЗЕД; загрози та можливості; нові ринки; diversification; diversification strategy; geographic structure of foreign economic activity; threats and opportunities; new markets; 658.8